Fenomena Marital Rape: Hukum dan Konsekuensinya dalam Perspektif Islam - Annisa Qurrota Aini; Riska Riyanni (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
This research is focusing on its law and its consequences according to The Islamic Perspective. The aim of this study is to provide an overview of marital rape, why the phenomenon occurs, how the Islamic perspective on marital rape is, and what are the consequences based on the Islamic perspective are. This type of research is mixed between quantitative and qualitative by conducting library research. The results obtained from this study are that the cause of the phenomenon of marital rape is the COVID-19 pandemic, the absence of regulations governing marital rape, and the existence of assumptions or rules that require married women to obey their husbands. The Islamic perspective on one of the rapes in marriage is discussed in Q.S. An-Nisa '(4): 34. Furthermore, sanctions for the marital perpetrators according to The Islamic perspective, the perpetrator will be given ta'zir sanctions which have not been determined by syara'. So, the determination will be submitted to ulil amri or judges.